Antibiotic use during pregnancy in Sweden: A nationwide utilization study covering 2007–2019 - Aya Olivia Nakitanda; Ingvild Odsbu; Björn Pasternak; Pär Karlsson; Laura Pazzagli (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Antibiotics are often prescribed during pregnancy. Assessing the current state of prenatal antibiotic use is therefore imperative for optimizing prescribing and identifying emerging research priorities. The study aimed to describe recent trends and patterns in antibiotic use during pregnancy among women who gave birth in Sweden, including user characteristics. Material and methods Population‐based descriptive study using linked nationwide registers. All pregnancies delivered in Sweden from 2007 to 2019 were included. Prevalence of use was defined as the percentage of pregnancies during which at least one prescription forantibiotics was filled. Temporal trends in the prevalence of antibiotic use by calendar year, trimester and weeks of gestation were assessed from time series graphs. Results Prescriptions for systemic antibiotics were filled in 20.7% of 1 434 431 pregnancies overall, decreasing from 24.7% in 2007 to 18.0% in 2019. Phenoxymethylpenicillin (8.5%), pivmecillinam (6.5%), nitrofurantoin (4.7%), amoxicillin (1.6%) and cefadroxil (1.5%) use were the most prevalent. Their use decreased over the 13‐year period, except for pivmecillinam, which increased from 4.0% to 7.4%. Prevalence of use was highest in the second trimester (9.5%), with weekly trends peaking at 13 and 34 weeks of gestation. Compared with non‐users, antibiotic users more often belonged to the youngest and oldest age strata, carried multipleton pregnancies, had delivered before, had attained a lower education level and smoked in early pregnancy. A higher body mass index, asthma, chronic renal disease and diabetes mellitus were more prevalent among antibiotic users than among non‐users. Conclusions Although outpatient antibiotic use during pregnancy in Sweden has been declining, one in five pregnancies was exposed to systemic antibiotics.